1998
DOI: 10.1128/iai.66.3.1135-1141.1998
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Binding and Elimination by Monocytes: Secretion of Soluble CD14 Represents an Inducible Mechanism Counteracting Reduced Expression of Membrane CD14 in Patients with Sepsis and in a Patient with Paroxysmal Nocturnal Hemoglobinuria

Abstract: Little is known about the role of peripheral blood mononuclear cells (PBMCs) in lipopolysaccharide (LPS) elimination. We studied the endotoxin elimination capacities (EEC) of PBMCs of 15 healthy volunteers, 13 patients with sepsis, and 1 patient suffering from paroxysmal nocturnal hemoglobinuria (PNH). Although expression of CD14, the best-characterized receptor for LPS to date, was reduced from 93.6% ± 0.8% in healthy subjects to 50.5% ± 6.5% in patients with sepsis and was 0.3% in a patient with septic PNH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 53 publications
0
30
0
1
Order By: Relevance
“…LPS activation causes the shedding and secretion of sCD14, thereby making sCD14 an important marker of LPS bioactivity. [38][39][40] Yokoyama et al 41 reported that human intrahepatic biliary epithelial cells constitutively expressed transcripts encoding TLR 1-6, TLR 9…”
Section: Histological Findingsmentioning
confidence: 99%
“…LPS activation causes the shedding and secretion of sCD14, thereby making sCD14 an important marker of LPS bioactivity. [38][39][40] Yokoyama et al 41 reported that human intrahepatic biliary epithelial cells constitutively expressed transcripts encoding TLR 1-6, TLR 9…”
Section: Histological Findingsmentioning
confidence: 99%
“…This form is stored intracellularly and is released spontaneously upon a short temperature shift at 37 ЊC; a process that is not altered by the presence of protease inhibitors [19,44]. Elevated levels of this 55-kDa sCD14 are detected exclusively in the sera of patients suffering from Paroxysmal Nocturnal Hemoglobinuria (PNH), whose monocytes do not express mCD14 as a result of a defect in GPI synthesis [44,46]. The enhanced release of sCD14 by monocytes of PNH patients might counteract the reduced mCD14 expression, as in vitro PNH monocytes are able to bind and respond to LPS in the presence of sCD14 [46].…”
Section: Release Of Different Forms Of Scd14mentioning
confidence: 99%
“…Elevated levels of this 55-kDa sCD14 are detected exclusively in the sera of patients suffering from Paroxysmal Nocturnal Hemoglobinuria (PNH), whose monocytes do not express mCD14 as a result of a defect in GPI synthesis [44,46]. The enhanced release of sCD14 by monocytes of PNH patients might counteract the reduced mCD14 expression, as in vitro PNH monocytes are able to bind and respond to LPS in the presence of sCD14 [46]. The biological differences between these two forms of sCD14 molecules are not clear yet.…”
Section: Release Of Different Forms Of Scd14mentioning
confidence: 99%
“…Complex interactions between LPS, CD14, myeloid differentiation-2 (MD-2) and Toll-like receptor (TLR)-4 results in an activation of the nuclear factor kappa-lightchain-enhancer of activated B cells (NFkB) signalling pathway and production of multiple inflammatory factors [24][25][26][27]. The MD-2/TLR-4/LPS complex induces shedding and secretion of soluble CD14 (sCD14) from myeloid cells [28][29][30]. Plasma or serum levels of sCD14 are generally accepted as reliable markers of bacterial translocation and endotoxaemia [24,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%